TEKNOLOGI EFISIENSI EKONOMI USAHA TAMBAK UDANG DI KECAMATAN MUARA JAWA KABUPATEN KUTAI KARTANEGARA - Handayani Boa; Nurul Ovie Oktawati; Zul Asman Randika (Fakultas Perikanan Dan Ilmu Kelautan Universitas Borneo Tarakan, 2017)
Delta Mahakam is one of the central representative aquaculture activities for Muara Jawa people that when this condition tend to be less technically efficient for production activities. The importances of this study through research objectives are (1) to analyze locative and economic efficiency achieved in the operations of farmers, (2) Measuring the use of production factors in optimal conditions to achieve a high economic efficiency level. The data in the second phase will be collected and then tabulated and analyzed, and to identify conditions and problems of shrimp farms by descriptive analysis. The results show on average the shrimp farmers in the study area have been technically efficient, but not locative and economically efficient. This is due to the excessive use of inputs that are less efficient. Increased production can increase the cost of production, so it is necessary to do the expansion of business scale in accordance with the recommendations allocative and economic efficiency. The shrimp fry price factor, the use of fertilizers and land depreciation expense does not significantly affect the cost of production so that if there is an increase in prices to a certain extent can be tolerated. The frontier analysis results showed most levels of price and economic efficiency of farms in the study area is relatively small or not efficient respectively 0.464 and 0.247, and the conditions of production factors are not the optimal conditions for below-average economic efficiency 0.664.Keywords: Economic Efficiency, Shrimp Farms, Muara Jawa